Pelaksanaan pendidikan profesi guru dalam jabatan pada universitas tanjungpura di mata peserta - Isti Dwi Puspita Wati; Toho Cholik Mutohir; Suroto Suroto; Y. Tauvan Juni Samodra (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2022)
This study aims to analyze teacher perceptions in the implementation of online-based teacher professional education (PPG) programs during the COVID-19 pandemic. This research uses descriptive quantitative research methods. The subjects used in this study were PPG Physical Education participants at Tanjungpura University. The sampling technique used is purposive sampling, where the sampling technique of data sources is carried out with certain considerations. The data collection technique in this study used a questionnaire that was distributed in the form of a google form to PPG Physical Education participants. Data analysis technique using descriptive. The results of this study indicate that the average perception of teachers in the process of implementing PPG material is 3.98 which indicates that the participants' perceptions are very good in the implementation of the online learning process carried out. Meanwhile, the teacher's perception of the pedagogical skills of the teaching staff is on average 3.97 which indicates that the pedagogical skills of the teaching staff are very good. Conclusion; In the eyes of teacher participants, the implementation of PPG at Tanjungpura University is included in the very good criteria, this can be seen from the average participant who gave a score of 3.9.